2011
DOI: 10.1093/annonc/mdr037
|View full text |Cite
|
Sign up to set email alerts
|

Metformin in prostate cancer: two for the price of one

Abstract: Overall available data support the potential dual benefit of metformin on ADT-induced metabolic syndrome and in its antineoplastic activity in prostate cancer, justifying the need for ongoing clinical trials to confirm these effects as the evidence currently available for standard practice is lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 57 publications
0
45
0
Order By: Relevance
“…12 Recently, metformin has been reported to hold potential for cancer treatment. [13][14][15] The anticarcinogenic affects appear to be associated with the regulation of NF-jB, matrix metalloproteinase (MMP)-2/9, AKT (also known as protein kinase B), and extracellular-signalrelated kinase (ERK)1/2 signaling pathways that are known to be important mediators of inflammation, tumor invasion and metastasis. 16 Recently, Quaile et al 17 reported that the no observable adverse effect level of metformin was 200 mg/kg/d (mean area under the curve 0-24 ¼ 41.1 lg h/mL; mean Cmax ¼ 10.3 lg/mL based on sex average week 13 values) in rats.…”
Section: Discussionmentioning
confidence: 99%
“…12 Recently, metformin has been reported to hold potential for cancer treatment. [13][14][15] The anticarcinogenic affects appear to be associated with the regulation of NF-jB, matrix metalloproteinase (MMP)-2/9, AKT (also known as protein kinase B), and extracellular-signalrelated kinase (ERK)1/2 signaling pathways that are known to be important mediators of inflammation, tumor invasion and metastasis. 16 Recently, Quaile et al 17 reported that the no observable adverse effect level of metformin was 200 mg/kg/d (mean area under the curve 0-24 ¼ 41.1 lg h/mL; mean Cmax ¼ 10.3 lg/mL based on sex average week 13 values) in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in these compounds has been increased over the years. Several reports have shown greater type 1 and 2, 5α reductase expression in higher grade PCa [29] and due to the incidence of metabolic syndrome in PCa patients receiving ADT [30][31][32]. As specific alterations in intracellular pathways were observed with combination treatment compared to each compound alone, further investigation in this process is required with both androgen dependent and independent prostate cancer cells.…”
Section: Metforminmentioning
confidence: 99%
“…From the point of cancer prevention, metformin can be viewed as a “hybrid” drug. Not only it lowers the concentration of potential cancer “ligands” in the bloodstream (such as glucose and insulin), but also acts within the cell suppressing the AMPK/mTOR/p70S6K1 pathway [52], including specifically in PCa cell lines [53]. More recently, IGFR and p53 mediated mechanisms of its anticancer action were reported [54].…”
Section: Pca Chemoprevention In Aammentioning
confidence: 99%